Space and Identity in J. G. Ballard’s Urban Disaster Fiction - Tereszewski, Marcin (Polish journal of English studies, 2019)
The confluence of spatiality and identity has been one of the central issues in psychogeographical research. J.G. Ballard’s fiction offers a valuable entry point into such considerations, especially when viewed alongside theoretical developments in the field of spatiality studies. In approaching the topic of identity disintegration in Ballard’s High-Rise and Concrete Island, this article attempts to present the complicit role the environment plays in self-determination. Though psychoanalysis has traditionally served as the first-line approach to Ballard’s work, spatiality studies offers an invaluable theoretical context, in which to further flesh out relationship that exists between the alienation, violence and isolation experienced by the characters and the particular environment they find themselves occupying.